The Role of Hippo Pathway as a Non-genetic Mechanism of Acquired Resistance to Targeted Therapies - Kouru, Ira (My University, 2023)
Almost half of melanomas are driven by mutations in the gene encoding a MAPK pathway kinase BRAF. The current standard of care in these tumors relies on the inhibition of BRAF in combination with the downstream kinase MEK. However, resistance to these inhibitors develops rapidly and inevitably. An urgent need for new therapeutics has led researchers to study the underlying mechanisms of treatment resistance. One proposed escape mechanism has been the activation and nuclear localization of YAP, the co-activator of the TEAD transcription factors. YAP-TEAD transcriptional activation regulates cell proliferation and inhibition of apoptosis. Here, BRAF-driven A375 melanoma cells were treated with the BRAF inhibitor dabrafenib and MEK inhibitor trametinib. Already after 3 days, dabrafenib alone or in combination with trametinib (DT) diminished cell number and decreased proliferation. The effect was more pronounced after 7 days of treatment. ERK phosphorylation, which was used as the readout of MAPK pathway activity, was inhibited by dabrafenib and even more by DT, as expected, and the effect was highest on day 3. In addition, clear morphological changes were seen, and the cells changed toward an EMT-like phenotype. Furthermore, a 3-day treatment with dabrafenib or DT increased TEAD-target gene expression, suggesting activation of YAP-TEAD. After continuous DT treatment for over 2 months, the cells, hereby referred to as A375-DT, became partly resistant to the treatment and resumed proliferation. In these A375-DT cells, ERK phosphorylation was lower than in parental cells, while YAP nuclear localization and TEAD target gene expression were modestly, but significantly, enhanced. Hence, the activation of YAP-TEAD may be one of the mechanisms leading to DT treatment resistance. As a next step, compounds that have been shown to bind TEAD and inhibit its transcriptional activity, here referred to as TEAD inhibitors (TEADi), were used. When TEADi were combined with DT in parental cells, TEAD inhibition only modestly inhibited cell growth in comparison to the DT treatment alone. However, when TEADi were combined with DT in the A375-DT cells, a significantly higher, yet partial, inhibition of cell growth was observed. Importantly, TEADi decreased the YAP-TEAD target gene expression in A375-DT cells. Together these results suggest that although YAP-TEAD is activated, the A375 cells use also other resistance mechanisms. Thus, further studies in other BRAF mutant melanoma cell models are needed to determine the relevance of TEADi in combination with standard of care (BRAF and MEK inhibitors) in the treatment of melanoma patients.
Keywords: Melanoma, YAP, TEAD, BRAF, MEK, Hippo pathway